MAPPING GRAMMATICAL ERRORS IN SPEECH PRODUCTION OF JUNIOR AND SENIOR STUDENTS: A CASE STUDY - Maraden Marcellino (Indonesian JELT, 2012)
Acquiring a foreign language requires a student to master the two elements of language, vocabulary and grammar, and the four language skills, listening, speaking, reading, and writing. Within each skill, these two language elements play a considerably essential role since they are seen as the very core aspects of language learning and that they are regarded inherent in each of these skills. Thus, vocabulary and grammatical aspects cannot be separated from the four language skills in language acquisition as without any one of which each skill is never acquired. Since the implementation of communicative approach in 1984 to the application of the competency-based language teaching in Indonesia, English programs at high schools have been meaning or message based rather than language usage or form oriented. As a result, grammar learning has been significantly kept aside if not totally ignored in class interactions, and that communication success becomes the main target in instructional objectives. This study attempts to map grammatical errors the students make in their speech productions. It employs an interview technique for data collection by recording the conversations of twenty respondents - - junior and senior students - - on a selected issue of a particular topic and transcribing them in the form of written transcripts which are then to be analyzed from a grammatical perspective with the reference of grammar books. Those violating the grammatical norms will be considered as grammatical errors. It has been found out that learners’ grammatical errors are derived from two major causes - - translating concepts of L1 into L2 and their approximative system. This study concludes that the communicative classrooms which utilize the competency-based language teaching bring about a positive impact upon grammar learning. This research is significant as it gives a great contribution to structure and speaking class teachers, students, as well as to the department for policy making.